Los colores y su semàntica en las expresiones fraseológicas españolas - Szałek, Jerzy (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2005)
Analysis of Spanish idiomatic expressions containing chromatic components provides us with more knowledge of the structure of the modern Spanish phraseology. Studying the difficult to perceive semantic interdependence occurring between the compounds of a given type, allows us to draw a few vital conclusions and also to present the specific character of the Spanish language in respect of perceiving and understanding the world through the symbols of colors (Sp."idiosincrasia española"). From the point of view of phraseology, Spanish phraseological units containing colors display various degrees of both stability and idiomaticity and their ultimate meaning can be diverse; on occasions they can even be opposite in meaning in the frame of a given type
Colors and their semantics in Spanish idiomatic expressions